ANALISA PENGARUH KOMPETENSI, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA GURU PADA SMK SASMITA JAYA 1 PAMULANG KOTA TANGERANG SELATAN - Mukhlis Catio; Denok Sunarsi (Universitas Kuningan, 2020)
The purpose of this study was to determine the effect of partially or simultaneously between Competence, Work Discipline and Motivation Against Teacher Performance at Sasmita Jaya 1 Vocational School Pamulang, South Tangerang City. The method in this research is associative type with descriptive and quantitative approaches. The population and sample in this study were 108 respondents and used census sampling techniques to determine the number of samples. The analytical tool uses multiple linear regression analysis with the help of SPSS 24 Software. The results of the study found the level of influence between the variables of competence, work discipline and motivation on performance of 0.731 and enter into intervals between 0.600-0.799 with a strong influence level, meaning competence, work discipline and motivation has a strong level of influence on performance. And the contribution of competence, work discipline and motivation to performance by 53.5% and the remaining 46.5% is influenced by other factors outside the research variable model such as compensation, training, work environment and others. Of the three independent variables (competence, work discipline and motivation), the work discipline variable had the biggest contribution to performance by 47.5% and the lowest contribution was given the competency variable by 36.3%